Pharmacological justification for the ethnomedical use of Clausena anisata root-bark extract in the management of epilepsy - Kenechukwu FC, Mbah CJ, Momoh MA, Chime SA, Umeyor CE and Ogbonna JDN (Journal of Applied Pharmaceutical Science)
Various morphological parts of the tropical plant, Clausena anisata (Wild) Hook [Family: Rutaceae], have ethnomedical claim for use in the management of epilepsy. This study examined the antiepileptic activity of Clausena anisata root bark, stem bark and leaf ethanolic extracts (i.e. CARE, CASE and CALE respectively) against pentylenetetrazole (PTZ) induced seizures in mice. Phytochemical and acute toxicity tests were performed on the extracts followed by oral administration of graded doses of CASE (500, 750 and 1000 mg/kg), CARE and CALE (400, 600 and 800 mg/kg) to the mice, thirty minutes before the administration of PTZ (90 mg/kg i.p.). The anticonvulsant effect of the extracts and diazepam (4 mg/kg) were compared. CALE was found to possess large amount of saponins, CARE large amounts of tannins and saponins, CASE large amounts of flavonoids, alkaloids and tannins. While CARE at the dose level of 800 mg/kg significantly (p
Keywords: Anticonvulsant activity, Clausena anisata, pentylenetetrazole (PTZ), phytochemical tests.